Efeitos do glúten de trigo em modelo de colite experimental - Penélope Lacrísio dos Reis Menta (2018)
Objectives: Studies have shown that gluten is only partially digested by enzymes of gastrointestinal tract, which could lead to the accumulation of potentially toxic intestinal waste that can alter intestinal permeability and affect the immune system. Although wheat gluten exerts effects on the intestine, there are as yet no studies on its role in its possible interference with the evolution of ulcerative colitis. Thus, the objective of this work was to investigate the effects of a diet containing wheat gluten in an experimental model of colitis, as well as to evaluate what are the mechanisms mediated by it. Methods: C57BL / 6 mice, healthy or with colitis induced by sodium dextran sulfate (DSS) were fed: standard diet (Control and Colitis groups), diet containing 4.5% gluten (Control + Gluten or Colitis + Gluten) or modified with wheat flour (Control + Flour or Colite + Flour). The DSS solution (1.5% w / v) was used instead of water from the 7th to the 15th day of the experiment. Analyzes of weight variation, clinical score, histopathological score, indirect analysis of the inflammatory cell profile (neutrophils, eosinophils and macrophages), intestinal permeability, bacterial translocation, analysis of the junctional complex and their proteins were performed. Results: Gluten, specifically, caused worsening of the clinical score, increased recruitment of neutrophil and eosinophilic effector cells, increased intestinal mucosal inflammation, increased intestinal permeability, increased bacterial translocation, both by the paracellular and the transcellular pathways. The mechanism by which gluten exacerbated colitis appears to be related to changes in adhesion junction and desmosomes, especially the α-E-catenin protein, which resulted in compromising the localization of E-cadherin, β-catenin proteins and weakening of desmosomes. There was also greater epithelial damage caused by gluten, with alteration of microvilli, a greater amount of digestive vacuoles and alteration of the endosome/lysosome system. Conclusion: Our results show that gluten specifically exerts a deleterious effect on colitis and its mechanisms seem to be related to changes in the adhesion junction, desmosomes, in microvilli and vesicles of the endocytic route.